Performance Analysis of a Horizontal Axis Spiral Type of Solar Collector Made of Copper Pipe on Solar Energy Absorption - Akhyar, Mahmud; Pranoto, Siswo; Malau, Muhammad Fadlan (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2025)
Renewable energy is a sustainable and inexhaustible energy source that can be obtained from water, wind, ocean waves, and solar radiation. Among them, solar energy is an abundant and underutilized resource. This study aims to investigate the heat transfer process from the evaporator pipe to the heated water and to analyze the performance of a horizontal-axis spiral-type solar collector. The results show that the collector effectively absorbs solar energy even under cloudy or rainy conditions, with the highest energy absorption of 35,700 J recorded between 12:00–13:00 WIB. Under cloudy weather, the maximum energy absorbed was 31,500 J between 15:00–17:00 WIB, while under hot conditions, the same energy value (31,500 J) was achieved between 11:00–17:00 WIB. This indicates that solar energy absorption largely depends on the temperature difference (?T) between the collector’s inlet and outlet water temperatures.